Síntese, caracterização estrutural e estudo fotofísico de cromóforos diflúor-organoboro derivados de azaheterociclos - Calheiro, Tainara Paulus (2018)
The present work presents the synthesis and spectroscopic study of new oxadiazaborinine derivatives from 2-amino substituted azaheterocycles systems, subdivided into four different classes of azaheterocycles, these are comprised of naphthyridine, pyridine, pyrimidine and quinoxaline systems. The four substituted 2-amino systems were initially converted to the respective amides from the N-acylation reactions and then used for the conversion to the difluoro-organoboron heterocyclic systems derived in reactions with BF3.Et2O. Initially, the novel N-(1,8-naphthyridinyl) benzamide precursor blocks were obtained n yields of 65 – 92 %. From these systems and N-(1,8-naphthyridinyl) acetamides analogous derivatives, reactions were carried out with BF3.Et2O to obtain the respective difluororganoboro derivative heterocycles in yields of from 50 – 66 %. Subsequently, reactions of (N-pyridinyl) benzamides and (N-pyrimidinyl) benzamides with BF3.Et2O provided the isolation of two new analogous series in yields of 51– 70 % and 50 – 68 %, respectively. Finally, novel benzamides derived from 2-aminoquinoxalines systems were obtained in yields of 62 – 82 % and were sequentially used as precursor blocks for the synthesis of novel difluoro-organoboro heterocycles by reaction with BF3.Et 2O. In the course of the synthesis of the four series of difluoro-organoboron heterocycles, the structural characterization of the unpublished molecules was performed by 1H, 13C, 19F and 11B NMR, two-dimensional experiments HMBC 1H-15N, GC-MS, X-ray diffraction in monocrystals and analysis elementar CHN. In parallel, photophysical properties such as absorption, emission, fluorescence quantum yield, Stokes shifts and cyclic voltammetry properties were performed, presented and discussed. Interaction assays of these heterocycles with ct-DNA and BSA, as well as molecular docking and theoretical calculations complemented the present study.